Effect of tyrosinase and caffeic acid crosslinking of turbot parvalbumin on the digestibility, and release of mediators and cytokines from activated RBL-2H3 cells. (1st December 2019) - Ahmed, Ishfaq; Ma, Jiaju; Li, Zhenxing; Lin, Hong; Xu, Lili; Sun, Lirui; Tian, Shenglan
Highlights: Tyr and CA treatments of turbot PV resulted in crosslinks formation. Crosslinking caused changes in the SGF and SIF digestion stability of PV. Both treatments reduced the release of cellular mediators and cytokines. Tyr and CA treatments shown promise in developing hypoallergenic fish products. Abstract: Turbot can induce allergy in susceptible individuals due to the presence of parvalbumin (PV), a major fish allergen. This study aimed at evaluating the digestibility and the ability of PV to elicit the release of cellular degranulation, following treatment with tyrosinase (PV-Tyr), caffeic acid (PV-CA) and in combination (PV-Tyr/CA), using in vitro digestion and RBL-2H3 (passive rat basophil leukemia) cell line. The digestion assay products revealed that the stability of PV in simulated gastric fluid (SGF) was stronger, while in simulated intestinal fluid (SIF) was rather weak. Western blot analysis revealed that the IgG-binding abilities of the cross-linked PV were markedly reduced. Moreover, crosslinking hampered the release of cellular degranulation process in RBL-2H3 cell lines. PV-Tyr/CA showed highly significant reduction in the release rate of β -hexosaminidase (66.02%), histamine (35.01%), tryptase (29.25%), cysteinyl leukotrienes (29.72%), prostaglandin D2 (34.96%), IL-4 (43.99%) and IL-13 (38.93%) and shown potential in developing hypoallergenic fish products.